Contract farming : short case study of silk worm production in Lundu district - Anthony, Aboi. (Universiti Malaysia Sarawak (UNIMAS), 2002)
This short field investigation will assess the Contract Farming of silk worm production in Lundu District, Sarawak with the general objective to assess the income distribution of the project to the household of those participants. The study will also examine the level of participation of those farmers as far as their involvement in the project is concerned.